2016
DOI: 10.1016/j.carbon.2015.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of graphene-on-insulator films formed using plasma based surface chemistry

Abstract: This research explores the surface chemistry of halogen based plasmas on silicon carbide and is aimed at the synthesis of large area graphene-on-insulator films. In these studies, 6H-SiC (0001) substrates were etched using either CF4 and Cl2 based plasmas and then thermally annealed. The resulting surfaces were analyzed using x-ray photoelectron spectroscopy, reflection high energy electron diffraction, atomic force microscopy, and Raman spectroscopy. The analyses showed that the etching process selectively et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…On the other hand, the deformation of Dirac cones for the AAB-and sliding bilayer configurations [64,66,148] can be verified by using ARPES. The aforementioned electronic characteristics have also been confirmed in absorption [164, 166-168, 173, 174, 177], transmission [180,181], refection [136], Raman scattering and Rayleigh scattering spectroscopy [75,76,138,139,171,172,[236][237][238][239][240][241][242][243]. The evidence of Dirac cones has been observed for monolayer graphene in terms of the zero threshold frequency and the linear dependence of the intensity on the frequency.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…On the other hand, the deformation of Dirac cones for the AAB-and sliding bilayer configurations [64,66,148] can be verified by using ARPES. The aforementioned electronic characteristics have also been confirmed in absorption [164, 166-168, 173, 174, 177], transmission [180,181], refection [136], Raman scattering and Rayleigh scattering spectroscopy [75,76,138,139,171,172,[236][237][238][239][240][241][242][243]. The evidence of Dirac cones has been observed for monolayer graphene in terms of the zero threshold frequency and the linear dependence of the intensity on the frequency.…”
Section: Introductionmentioning
confidence: 75%
“…The electronic properties are studied by use of STM, STS [6-9, 11] and ARPES [10,[68][69][70][71][72][73][74][75][76]. The band structures based on the tight-binding model agree with the first principles calculations [64, 66, 77, 78, 80-84, 89, 90, 93, 94, 96, 148].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, some novel methods are emerged to prepare graphene membranes. For example, Raghavan et al [58] used plasma to prepare graphene membranes on the substrates including 6H-SiC etched by CF 4 -and Cl 4 -based plasmas and the results showed that the etching process could selectively etch silicon to produce carbon-rich surface layers on the silicon carbide substrate. When annealed, these carbon-rich layers formed graphene films with halogen-and oxygen-based defects.…”
Section: Graphene and Go For Gaseous Selectivity Separationmentioning
confidence: 99%
“…The synthesized graphene generally comprises different kinds of domains due to the tiny difference among the total energies of different configurations. Infrared spectroscopy, transmission electron microscopy (TEM) [3-5,34], scanning tunneling microscopy (STM) and spectroscopy (STS) [6-9, 11, 35-37], angle resolved photoemission spectroscopy (ARPES) [62][63][64][65][66][67][68], and Raman spectroscopy [10,69,70], are used to visualize stacking domains with a namometric resolution for cases of tri-, tetra-, and pentalayer graphene with typical or intermediate configurations.Monolayer graphene belongs to a gapless system which possesses extremely high carrier mobility of up to 15,000 cm 2 V −1 s −1 [1]. P. R. Wallace has discovered that the low-energy 1 spectrum around the corners K and K in the Brillouin zone is described by isotropically conical dispersions in the framework of the nearest-neighbor tight-binding model [71].…”
mentioning
confidence: 99%